Effect of Product Attributes, Promotions, and Motivation on Subsidized Home Buying Decisions - Jaelani, Raditya; Yuliati, Lilik Noor; Sartono, Bagus (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
Subsidized housing is a government program with the aim of meeting the housing needs of low-income peoplewhere subsidies or housing financing assistance are in the form of houses with selling prices below market prices. However, companies that develop subsidized houses must now be able to survive during increasingly fierce business competition conditions and world economic conditions that are being shaken by the Covid-19 pandemic. People's purchasing power that has decreased due to the rules for "Stay at Home" has made all areas of the economy decrease. Sentra Hills Tenjo is one of the many subsidized housing estates developed by housing developers. This housing is under the auspices of PT Bogor Indonesia Depeloper as the developer. This housing is in Singabangsa, Tenjo District, Bogor, West Java. This housing offers two types of houses, namely type 24/66 and type 36/72. The purpose of this study is to identify the characteristics of buyers who have made subsidized home loan agreements in Perumahaan Sentra Hills Tenjo., Analyze the influence of product attributes, promotions, and motivations on the decision to buy subsidized houses in Sentra Hills Tenjo and Formulate managerial implications for increasing the number of subsidized home purchases in Sentra Hills Tenjo. Analysis using Structural Equation Modelling. The results showed that product, promotion and motivation variables influenced the decision to buy subsidized houses in Sentra Hills Tenjo Housing.